2019
DOI: 10.1177/1120700019832877
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumours, cobalt and clinical outcome in small head metal-on-metal versus conventional metal-on-polyethylene total hip arthroplasty

Abstract: IntroductionTotal hip arthroplasty (THA) has proven to be an excellent treatment for treating osteoarthritis of the hip. Since Sir John Charnley, the metal-on-polyethylene (MoP) bearing has been the gold standard, outperforming 1st-generation metal-onmetal (MoM) THAs like the McKee THA. 1 However, polyethylene (PE) wear leading to particle-induced osteolysis and component loosening has been considered a drawback of the MoP articulation couple. Therefore, in the late 1980s, 2ndgeneration MoM bearings were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…However, when using uncemented Biomet cups (PE+M2a or PE) the liner was attached to the acetabular component by RingLoc mechanism, producing intraoperative modularity comparable to the monoblock Stanmore cup. Implant survival in our study for both M2a and MoP THA groups was slightly inferior compared with those of van der Veen et al ( 12 ) but their study patients initially participated in a single-center trial whereas our data represents nationwide results. Difference in fixation method may also have some minor bias on the results.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…However, when using uncemented Biomet cups (PE+M2a or PE) the liner was attached to the acetabular component by RingLoc mechanism, producing intraoperative modularity comparable to the monoblock Stanmore cup. Implant survival in our study for both M2a and MoP THA groups was slightly inferior compared with those of van der Veen et al ( 12 ) but their study patients initially participated in a single-center trial whereas our data represents nationwide results. Difference in fixation method may also have some minor bias on the results.…”
Section: Discussioncontrasting
confidence: 83%
“…Previous reports focus mainly on devices under the same product umbrella with notable differences. Van der Veen et al ( 12 ) reported similar 96% implant survival rates at 13 years when comparing 23 cemented M2a THAs and 33 cemented MoP THAs. A Stanmore cemented stem was used in both groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although pseudotumours have been studied extensively [5,[12][13][14][15], little is known about their natural history and controversy exists over their management, especially in asymptomatic patients [3,13,16]. Reports in the literature show that pseudotumours can grow in size, remain static, reduce in size and spontaneously resolve [13,16,17].…”
Section: Introductionmentioning
confidence: 99%